The impact of medium acidity on the chronological life span of Saccharomyces cerevisiae – lipids, signaling cascades, mitochondrial and vacuolar functions. (21st January 2014) - Yucel, Esra B.; Eraslan, Serpil; Ulgen, Kutlu O.
<x xml:space="preserve">Abstract</x> Because of its multifactorial nature, aging is one of the most complicated cell phenomena known. A systems biology approach, which aims to understand the organism as a whole rather than concentrate on the behaviors of individual genes, thus comprises a seamless tool for investigating the aging machinery, which arises mainly as a result of degeneration of the collaboration between signaling and regulatory pathways. In the present study, the effects of medium buffering on the chronological life span are investigated via transcriptome analyses and subsequent integration of the data obtained with the chronological aging network of yeast. The comparative inquiry of transcriptome data of young and old cells grown in buffered and unbuffered media reveals new roles for pH control (e.g. the re‐organization of lipid metabolism and intracellular signaling cascades) that have beneficial consequences on chronological longevity. Integration of the transcriptome data onto the aging network, as well as validation experiments, suggest that Snf1p is a possible intermediate player in the interjunction of sphingolipid and ergosterol metabolisms with extracellular pH control with respect to regulation of the chronological life span. Consequently, a more detailed insight of the chronological aging mechanism of yeast is obtained. The results of the present study provide a solid basis for further research focusing on uncovering the agents that affect aging and age‐related diseases in humans.